The Role of ChatGPT in Writing Performance: A Review of Recent Studies - Arbi, Anggun Purnomo (Jujurnal Publisher, 2024)
Learning in the digital era has been influenced by the technological revolution, including the use of artificial intelligence (AI). One innovation in this regard is the use of ChatGPT as an AI-based platform to support the writing process. The purpose of this study is to identify and analyze recent findings regarding the use of ChatGPT in supporting the writing process, as well as to evaluate the contribution of ChatGPT in improving the quality and efficiency of writing performance in various contexts. The research approach used was a systematic review of recent studies conducted using meta-analysis. The findings of this study show that the use of ChatGPT contributes significantly to improving writing skills, time efficiency, and the creative process of writing. The implication of these findings is the importance of integrating ChatGPT in writing education to broaden and deepen the understanding of language as well as the creative writing process, but it is also necessary to note the limitations and concerns regarding the use of ChatGPT in educational contexts